The Role of Lighting in The Interior Atmosphere of Saka Bistro and Bar Bandung - Michaela Maggie T; Tessa Eka Darmayanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2023)
The purpose of this study was to determine the impact of the role of lighting in creating an atmosphere that can explain certain themes and styles applied to the interior design of Saka Bistro & Bar Bandung, so that room users or space observers can see and feel the visualization. Lighting is an important factor that can give atmosphere and character to the interior. There are many types of lighting that can be used in a room, depending on the atmosphere the user wants to create. Lighting also helps visualize the style applied to the space. The method used in this study is the method used in this study qualitatively, in the form of observation and comparison based on the theory used in the study. The results and conclusions obtained are explained in detail using the researcher's observations which are then compared with the theory used. The conclusion obtained is that the role of lighting that is applied to the interior of Saka Bistro & Bar Bandung helps create an atmosphere that can describe the urban and tropical theme or style applied to the interior of the Bandung Bistro & Bar.